A study to compare three airway devices in relation to their effects on IOP and haemodynamic changes in anaesthetized patients - P B , Jamale; Bhaulekar, Shardha (International Journal of Psychosocial Rehabilitation, 2020)
The study was conducted on 120 patients aged 15-60 years of ASA grades I and II undergoing non-ophthalmic surgeries requiring general anesthesia. Patients were randomly allocated into I-GEL, C-LMA, and ETT groups. Each group contained 40 patients. The climb in IOP after incorporation of the contraption was progressively more conspicuous for the tracheal chamber intubation group (18.33+1.92 in the right eye and 18.54+2.0 in the left eye) than for the LMA group (13.15+1.85 in the right eye and 13.12+1.61 in the left eye) and the I-GEL pack, where there was no rising in any way, shape, or form (11.86+1.61 in the right eye and 11.72+1.60 in the left eye). The climb in HR after incorporation of the device was generally raised in the ETT group (99.2±8.39), followed by the C-LMA group (87.75±10.35), and there was fundamentally no rise in the I-GEL group (81.4+11.81). The climb in SBP after consideration of contraption stood out from after acknowledgment of regards (108.1+9.71, 107.17+9.14, and 108.05+7.23 for I-GEL, C-LMA, and ETT exclusively) was generally raised in the ETT group (130.57±8.16), followed by the old-style LMA group (117.95±7.39) (which didn’t rise above pre-enrollment regard), and essentially no rising in the IGEL group (108.77+9.10). The climb in DBP after consideration of contraption appeared differently in relation to after selection regards (69.22+9.82, 66.87+9.65, 69.12+9.72 for I-GEL, C-LMA, and ETT independently) was generally raised in the ETT group (84.52±11.78), trailed by the LMA group (79.27±7.31) (which didn’t rise above pre-acknowledgment regard), and for all intents and purposes no rise in the I-GEL group (69.8+10.01). Hence it was concluded that i-gel insertion produced the least rise in intraocular pressure and hemodynamic response as compared to laryngeal mask airway and tracheal intubation.